Políticas de educação linguística para o português em Guiné-Bissau: o ensino de gramática na perspectiva do material didático comunicar em português 6 e dos professores - Cunha, Marcelino Issa da (2024)
Language policies can be analyzed from official documents to textbooks, which function as implicit mechanisms for the dissemination of ideologies and linguistic practices. Our research aimed to investigate the teaching of grammar in the multilingual context of Guinea-Bissau from the perspective of teaching materials and Portuguese language teachers. To achieve this objective, we established the following questions that guide the research: how does the grammatical approach take place in the textbook Comunicar em Portuguese 6 and in the respective Activity Book? What is the perception of teachers about the teaching of grammar in general and the didactic material used for teaching Portuguese in the 6th grade? How can the grammar approach be improved to promote effective learning of the Portuguese language? To answer these questions, we based ourselves on Spolsky (2004, 2009, 2012, 2021) theoretical notion of language policy, which understands it from the dimensions of practices, beliefs, and management, as well as on Shohamy (2006, 2009) notion of language policy mechanism, especially in the mechanism of Language Education Policies, in which we consider textbooks as constituent of this mechanism. This research is characterized by its qualitative nature and is inserted in an interpretative paradigm (Lin, 2015), also characterized as documentary research (Cellard, 2012). The corpus consisted of the textbook "Communicating in Portuguese 6, being the Reading Book, and its respective Activity Book, as well as the discourses of nine Portuguese language teachers, generated from the application of a questionnaire. For the analysis of these discourses, we used thematic analysis (Braun; Clark, 2008). The results indicate that the teaching of grammar in Guinea-Bissau, as evidenced in the didactic material and in the teachers' discourses, is predominantly characterized by a metalinguistic approach and by a focus on the structural aspects of the language. In our view, textbook is a mechanism of linguistic policy, fostering, for teachers, the belief in the teaching of traditional grammar. With the proposition of the suggestions presented, it is expected that teachers will know other possibilities of teaching grammar that goes beyond the teaching of metalanguage. We conclude that it is essential to review teaching materials and grammar teaching practices to promote more effective and inclusive learning, which prioritize epilinguistic activities and consider students' knowledge of the Guinean language.